The role of ophthalmological examination in the diagnosis of gangliosidosis GM1 - Krzywińska-Zdeb, Elżbieta; Giżewska, Maria; Modrzejewska, Monika; Romanowska, Hanna; Stecewicz, Iwona; Pawłowska, Anna; Tuziak, Martyna; Walczak, Mieczysław (Klinika Oczna / Acta Ophthalmologica Polonica, 2011)
Gangliosidosis GM1 belongs to a group of lysosomal storage diseases and results from the deficiency of acidic β-galactosidase activity. The enzyme is essential for the degradation of ganglioside GM1 and its derivatives. The disease causes multi-organ injury, however accumulation of ganglioside GM1 mainly in the brain white and gray matter results in predomination of neurological symptoms. Based on the actual knowledge – the condition is untreatable and especially in the very severe infantile form, the duration of the survival is very short. One of the characteristic symptoms of some lysosomal storage diseases, including gangliosidosis GM1, is “cherry-red” spot found in the fundus of the eye. In the publication the clinical course of gangliosidosis GM1 in two infants is presented. The value of an ophthalmological examination in the diagnosis of this rare condition has been emphasized.